2004
DOI: 10.1002/cncr.20532
|View full text |Cite
|
Sign up to set email alerts
|

Death during induction therapy and first remission of acute leukemia in childhood

Abstract: BACKGROUND Despite improvements in supportive care, death due to treatment toxicity remains a significant problem for children treated for acute leukemia. METHODS To determine the causes of and risk factors for death unrelated to refractory leukemia, to disease recurrence, or to second malignancy, the authors reviewed the records of 1011 patients with acute lymphoblastic leukemia (ALL) and 260 patients with acute myeloid leukemia (AML) treated between 1984 and 1999 and between 1983 and 2002, respectively, at S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
114
4
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 31 publications
17
114
4
2
Order By: Relevance
“…The ALL-BFM Study Group reported similar death rates for their studies ALL-BFM-86 and À90, 17 as did other collaborative groups. 10,18,19 The MRC identified high initial WBC and DS as risk factors for treatmentrelated mortality, whereas in other series, age was the main prognostic factor. 10,19 The relatively low death rate due to infections in ALL patients might reflect the empiric use of broad spectrum antibiotics in case of neutropenic fever, as well as successful prevention of Pneumocystis carinii pneumonia.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The ALL-BFM Study Group reported similar death rates for their studies ALL-BFM-86 and À90, 17 as did other collaborative groups. 10,18,19 The MRC identified high initial WBC and DS as risk factors for treatmentrelated mortality, whereas in other series, age was the main prognostic factor. 10,19 The relatively low death rate due to infections in ALL patients might reflect the empiric use of broad spectrum antibiotics in case of neutropenic fever, as well as successful prevention of Pneumocystis carinii pneumonia.…”
Section: Discussionmentioning
confidence: 89%
“…10,18,19 The MRC identified high initial WBC and DS as risk factors for treatmentrelated mortality, whereas in other series, age was the main prognostic factor. 10,19 The relatively low death rate due to infections in ALL patients might reflect the empiric use of broad spectrum antibiotics in case of neutropenic fever, as well as successful prevention of Pneumocystis carinii pneumonia. 9,10 Some other cases of CRM may be readily preventable, such as accidental intrathecal vincristine administration.…”
Section: Discussionmentioning
confidence: 89%
“…Among patients with ALL in HICs, studies have identified gender, age, high white blood cell count, high-risk ALL, T-ALL, and Down's syndrome as TRM risk factors, although these have not been consistent (Wheeler et al, 1996;Rubnitz et al, 2004;Christensen et al, 2005;Slats et al, 2005). Conversely, Advani et al (1999) found that in the LIC of India, low haemoglobin, lymphadenopathy, and malnutrition were all associated with increased risk of TRM in ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have examined predictors of TRM in HICs (Wheeler et al, 1996;Riley et al, 1999;Creutzig et al, 2004;Rubnitz et al, 2004;Christensen et al, 2005;Slats et al, 2005), very few have looked at similar risk factors in LICs (Advani et al, 1999). Among patients with ALL in HICs, studies have identified gender, age, high white blood cell count, high-risk ALL, T-ALL, and Down's syndrome as TRM risk factors, although these have not been consistent (Wheeler et al, 1996;Rubnitz et al, 2004;Christensen et al, 2005;Slats et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation